Technopreneurial intention: peran self-efficacy, entrepreneurship education, dan relation support - Alamsyahrir, Dendy; Ie, Mei (Jurnal Manajemen Maranatha, 2022)
Technopreneurship is a trend in the future, precisely starting in the era of the industrial revolution 4.0. Technopreneurship is a concept that combines entrepreneurship and technology, followed by creativity and innovation. The number of technology-based entrepreneurs in Indonesia is currently only around 0.43% of the number of entrepreneurs in Indonesia, while the opportunity for technopreneurship is still very large and possible. This study aims to empirically examine the effect of self-efficacy variables on technopreneurial intentions, the effect of entrepreneurial education variables on technopreneurial intentions, and the effect of relation support variables on technopreneurial intentions in students of XYZ University. This study used 125 student samples selected through non-probability sampling with purposive sampling technique. The data analysis method in this study is a quantitative method using Structural Equation Model (SEM), which is processed with the help of SmartPLS 3.2.8 software. The results showed that self-efficacy had a positive and significant effect on technopreneurial intention with p-value of 0.000; entrepreneurship education has a positive and significant effect on technopreneurial intention with p-value of 0.004; and relation support has a positive and significant effect on technopreneurial intention with p-value of 0.000.